INTERNATIONAL POLICY AND MISSIONARY WORK IN THE CONDITION OF GLOBALIZATION (Scientific journal of the Fergana State University, 2023)
This article analyzes the views on international politics and missionary interaction in the context of globalization. The article also describes the ideological support and ensuring state sovereignty in some countries, as well as the encroachment on the constitutional system as a result of a mission led by international political centers around the world. It is evident that the missionaries are mobilizing huge investments in the struggle for ideological landfills. At the same time, it is clear that the missionary often follows brutal and destructive ideas in pursuit of well-defined political goals. As a result of these actions, under the guise of providing “free” aid to the economically backward states, it is seen as a secret manifestation of open interference with the internal affairs of some independent states.In today's difficult conditions, through ideological education, an instruction has been put forward to be always vigilant, sensitive and vigilant in the fight against any force that undermines the security of the country and the stability of society, its interests, and the future of the nation.